Translation and conflict a narrative account - Baker, Mona (Routledge translation classics, 2019)
"Translation and Conflict was the first book to demonstrate that translators and interpreters participate in circulating as well as resisting the narratives that create the intellectual and moral environment for violent conflict. Drawing on narrative theory and with numerous examples from historical and current conflicts, Mona Baker provides an original and coherent model of analysis that pays equal attention to the circulation of narratives in translation and to questions of dominance and resistance. With a new preface by Sue-Ann Harding, Translation and Conflict is more than ever the essential text for any student or researcher interested in the study of translation and political movements"--Provided by publisher.